(untitled) (Plant Tissue Culture and Biotechnology, 2018)
The endogenous bacterial contamination of plant tissue culture materials and their possible control was studied. Nine bacterial isolates were isolated from the contaminated tissue culture materials viz. potato and tea. On the basis of morphology and biochemical characters of nine isolates, seven were identified as Gram positive belonging to Bacillus alcalophilus, B. circulans, B. infantis, B. lentus, B. schlegelii, B. pumilus and B. subtilis. Remaining two were Gram negative and identified as Enterobacter cloacae sub. sp. dissolvens and Pantoea agglomerans. Molecular analysis was conducted on the basis of 16S rDNA sequence to confirm three isolates. Culture and sensitivity test was carried out to screen out the antibiotic sensitivity where streptomycin (S-10), polymyxin (PB-300) and gentamicin (CN-120) antibiotics were found to be effective against all bacterial isolates. The culture and sensitivity test reflected the feasibility to control or eliminate the contaminant bacteria during in vitro culture of plant which is very much required in the commercial tissue culture production. Plant Tissue Cult. & Biotech. 28(1): 99-108, 2018 (June)